1.  Theorem.
 Define  
P
 
n
(T ) =
 
u = 1
n
 
  (
n   - 1
u   - 1
)  
T
u
 
 
u !
 
,  
 
     
     
     
Φ
 
0  1
= e
3
 
2
t
 
1
 
,
 
     
     
     
Φ
 
n   α
=  
 
j
 
1
+... +j
 
α
= n
 P
 
j
 
1
(2t
 
1
)  ...  P
 
j
 
α
(2t
 
α
)  e
3
 
2
  (t
 
1
+... +t
 
α
)
 
 
 for  
n  1
,
 
     
     
     
Ψ
 
α
=
1
 
π
 d  log  
λ
 
1
 
q
 
1
- q
 
1
λ
 
1
 ...    
1
 
π
 d  log  
λ
 
α
 
q
 
α
- q
 
α
  λ
 
α
,
 Riemann 's  hypothesis  is  equivalent  to  the  upper  bound
 
     
     
       
lim  sup
 
n
  |  
 
α = 1
n
 
<   Φ
 
n   α
,   Ψ
 
α
  >
 
< Φ
 
0  1
,   Ψ
 
1
>
α +1
 
  |  
1
 
n
 
 
     
       1
 where   λ  is  the  modular  lambda  function,  
 
     
     
q
 
j
= e
i π   τ
 
j
 
 
     
     
τ
 
j
=  ie
t
 
j
 
 
     
      λ
 
j
= λ ( τ
 
j
),
 and  triangular  brackets  denote  integration  over  the  product  of  the  arcs  where  each   λ
 
j
 ranges  between  the  cusp  at  
1
 and  the  cusp  at  
0.
 
 
 
Proof.
 It  is  the  radius  of  convergence  at  
s =
3
 
2
  +  
1 +z
 
1 - z
 of  the  Maclaurin  series
 of  
π
s
 
 
 8   ζ (s ) ζ (s - 1 ) (1 - 4
1 - s
 
) Γ (s )
.  The  unit  disk  in  the  
z
 plane  maps  to  the  half - plane
 
 to  the  right  of  
3
 
2
.  Note  that  
α +1
 in  the  denominator  can  be  replaced  by  just   α.  The
 exponent  is  
3
 
2
 instead  of  
5
 
2
 since  
θ (ie
t
 
)
4
 
 dt =  
e
- t
 
 
π
 d  log  
1 - λ
 
λ
.
 
 
Remarks.
 
 1.  In  this  context,  one  of  Rieman 's  obserations  is  that  if  we  write  
 
     
     
      λ ' = 1 - λ
 
     
     
        τ ' =
- 1
 
τ
 
     
     
     
q ' = e
i π   τ '
 
 
     
     
     
t ' = - t
 then  for  any  two  values  
a, b
 of   λ,  say  with  
1   >  a   >  b   >  0
,
 
     
     
     
1
 
π
 
a
b
 
 e
(s - 1 )t  
 
 d  log  
λ
 
q λ '
  =  
1
 
π
 
a '
b '
 
 e
(s   -  1 )t '
 
 d  log  
λ '
 
q ' λ
.
 Since  
a ', b '
 are  in  the  reversed  order  it  is  convenient  to  write  it
 
     
     
     
     
      =
1
 
π
 
 
b '
a '
 
 e
(s - 1 )t '
 
 d  log  
q ' λ
 
λ '
.  
 We  like  to  have  the  lower  limit  be  the  larger  one.  In  order  to  make  a  well - defined  one - form
 which  descends  through  the  branching  at  the  point  where  
λ = 1 /2
,  which  maps  to  
j = 1728
,  
 we  must  choose  one  of  the  two  forms,  we  choose  
1
 
π
 d  log  
λ
 
q λ '
.  By  symmetry,  if  we  integrate
 
e
st - t
 
 times  this  form  along  the  path  where   λ  passes  from  
1
 to  
0
,  then  
j
 passes  from  
 infinity  to  1728,  the  
j
 invariant  of  the  Gaussian  integers,  and  back  again.  We  use
 the  same  form  for  both  halves  of  the  arc,  but  reverse  the  sign  of  the  form  on  the  
 return  journey  to  cancel  the  reversal  of  orientation  only.  This  defines  an  entire
 function  
h (s )
 which  satisfies  the  functional  equation  
h (s ) = h (1 - s )
,  and  
 our  L  series  satisfies
 
     
     
     
     
     
     
8 ζ (s ) ζ (s - 1 ) (1 - 4
1 - s
 
)   =  
π
s
 
 
Γ (s )
(  h (s ) +
1
 
s - 2
  -  
1
 
s
  ).
 Since  also  
1
 
s - 2
  -  
1
 
s
 is  symmetric,  the  whole  of  
8 π
- s
 
Γ (s ) ζ (s ) ζ (s - 1 ) (1 - 4
1 - s
 
)
 is
 invariant  under  
s  1 - s
.
 
 2.  Actually   ζ (s ) ζ (s - 1 )  satisfies  two  different  functional  equations.  The  one  we 've  seen  gives
 invariance  of   ζ (s ) ζ (s - 1 ) (1 - 4
1 - s
 
) Γ (s ) π
- s
 
 under  
s  2 - s
.  But  also  the  invariance
 under  
s  1 - s
 of  each  factor  in   ζ (s ) Γ (s /2 ) π
-
s
 
2
 
ζ (s - 1 ) Γ (
s - 1
 
2
) π
s - 1
 
2
 
 combined  with  the  invariance  
 under  interchanging  the  factors,  gives  invariance  of  the  product  also  under  
s    2 - s
.  From
 one  function  satisfying  two  functional  equations,  we  deduce  that  
2
1 - s
 
Γ (s ) Γ (1 - s /2 ) Γ (1 /2 - s /2 )
 must  satisfy  a  functional  equation  of  its  own.  That  is,  the  Gamma  function  satisfies  the  functional
 equation  that  
2
1 - s
 
Γ (s ) Γ (1 - s /2 ) Γ (1 /2 - s /2 )
 must  be  an  odd  function  of  
s
.  This  fact  is
 equivalent  to  the  Legendre  duplication  formula.
 
 3.  While   Ψ
 
α
 is  the  wedge  product  of  all  
1
 
i
d τ
 
j
  +  
1
 
π
 d  log  
λ
 
j
 
1 - λ
 
j
,  once  multiplied  out,  all  but  one
 of  the  resulting  integrals  is  non - convergent.  One  can  multiply  by  a  sequence  of  functions  
 tending  to  
1
 to  which  a  convergence  theorem  applies,  and  take  the  limit  of  
 convergent  integrals.  For  example,  multiplying  by  
e
- μ   (t
 
1
2
 
+... +t
 
α
2
 
)
 
,  which  is  a  product  of  functions
 of  the  separate  coordinates,  
 
<   Φ
 
n   α
,   Ψ
 
α
  >   =  lim
 
μ  0
 
u +v = α
p +q = n
  (
α
u
)C
 
q  v
( μ )  
 
j
 
1
+... +j
 
u
= p
 
 
s = 1
u
 
 
1
 
π
 
 
1
0
 
 P
 
j
 
s
(2t )  e
3
 
2
 t   -   μ  t
2
 
 
d  log  
λ
 
1 - λ
 where
 
     
     
     
C
 
q  v
( μ )   =
 
j
 
1
+.. +j
 
v
= q
 
 
s = 1
v
 
 
 
-
 
 P
 
j
 
s
(2t )  e
5
 
2
 t   -   μ  t
2
 
 
dt  .
 The  limits  in  the  first  integral  denote  that  the  integral  is  taken  as   λ  ranges  from  
 
1
 to  
0
.  Thus  
<   Φ
 
n   α
,   Ψ
 
α
  >
 is  a  limit  of  polynomials  of  degree   α  
 in  period  integrals  from  
1
 to  
0
 with  coefficients  which  are  known  quadratic  algebraic
 functions  of   μ.
 
 4.  I  would  like  to  thank  Robert  McKay  for  suggesting  this  problem.
 By  turning  back  to  what  I  think  may  have  been  Riemann 's  
 original  point  of  view,  techniques  reminiscent  of  wave  equations  might
 simplify  the  Merten  approach,  but  if  the  relation  with  cycles  and
 moduli  of  abelian  varieties  is  too  distant,  a  new  analytic  expression
 may  be  what  first  simplifies  Mertens '  calculation.
 
  |